Liquidity, Markets and Trading in Action An Interdisciplinary Perspective - Ozenbas, Deniz; Pagano, Michael S.; Schwartz, Robert A.; Weber, Bruce W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book addresses four standard business school subjects: microeconomics, macroeconomics, finance and information systems as they relate to trading, liquidity, and market structure. It provides a detailed examination of the impact of trading costs and other impediments of trading that the authors call (3z(Bfrictions(3y(B. It also presents an interactive simulation model of equity market trading, TraderEx, that enables students to implement trading decisions in different market scenarios and structures. Addressing these topics shines a bright light on how a real-world financial market operates, and the simulation provides students with an experiential learning opportunity that is informative and fun. Each of the chapters is designed so that it can be used as a stand-alone module in an existing economics, finance, or information science course. Instructor resources such as discussion questions, Powerpoint slides and TraderEx exercises are available online. .s
Chapter 1: Economics and the Equity Market: A Microeconomics Course Application -- Chapter 2: Liquidity, Trading, and Price Determination in Equity Markets: A Finance Course Application -- Chapter 3: Liquidity and the Impact of Information Shocks: A Macroeconomics Course Application -- Chapter 4: Trading and Technology: An Information Systems Course Application -- Chapter 5: Experiencing Market Dynamics with TraderEx: A Trading Decision-Making Simulation.
Keywords: Business enterprises$1 (BFinance.s; Finance; Microeconomics; Financial services industry; Corporate Finance; Financial Economics; Microeconomics; Financial Services